Anti-proliferative Effects of a Coumarin Benjaminin on Four Human Cancer Cell Lines - Mah, Siau Hui; Teh, Soek Sin; Ismail, Ahmad Azri Fitri; Ee, Gwendoline Cheng Lian (Pharmaceutical Sciences and Research, 2020)
Cancer is a major health issue around the globe. Chemotherapy and radiation therapy are no longer the standard treatments for patients as these remedies lead to many adverse effects. Thus, the development of alternative effective drugs from lead compounds, especially natural products is necessary. This study aimed to isolate cytotoxic phytochemical constituents from a plant Calophyllum inophyllum, which has been used as traditional medicine since ancient time. The root of C. inophyllum was extracted and subjected for phytochemical constituent isolation. A coumarin, benjaminin (1) was isolated successfully from the chloroform extract and its structural elucidation was performed by spectroscopy analyses of MS, IR and NMR. The anti-proliferative effect of 1 on four cancer cell lines, leukemia (K562), stomach (SNU-1), liver (Hep-G2) and lung (NCI-H23) cancers were evaluated by using colorimetric MTT assay. Benjaminin (1) exhibited cytotoxic effects towards all cancer cells and showed the strongest inhibition towards SNU-1 cell proliferation with an IC50 value of 70.42 μM. The outcome of this study revealed that 1 is a potential cytotoxic lead compound that could be further developed into anti-cancer drug. Thus, the study on the structure-activity relationship of 1 is highly recommended in due course to improve its anti-proliferative effects on cancer cells.